(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the effectiveness of membrane sweeping for induction of spontaneous labour at term. Material & Methods Design: A randomized controlled trial Setting: Dr. Ziauddin Hospital, Karachi, Pakistan Duration: August 5, 2012 to August 4, 2013 Sample Size: A total of 210 patients were included.105 patients were subjects and 105 were controls. Methods: Sweeping of membranes was performed 38 weeks onward till 40 weeks in cases and no intervention was done in controls till 41 weeks. Main Outcomes Measures the number of women having successful induction of labour by sweeping of membranes. the women who did not go in spontaneous labour and required pharmacological method for labour induction. to compare recruitment to delivery interval in study group. Results: In interventional group, 62.9% of swept women went into labour and 37.1% required labour induction with the methods other than sweeping while in the control group, 43.8% women went into spontaneous labour and 56.2% required their labour to be induced with the methods other than sweeping. Result found statistically significant (p<0.05). Conclusion: Sweeping of amniotic membranes from 38 weeks onward to induce onset of labour is an effective maneuver. It decreases the frequency of post date pregnancy and need to use pharmacological methods of labour induction which are not without risks to the mother and the fetus.